Dinamika Inflasi di Indonesia, Analisis Faktor-Faktor Penyebab dan Dampaknya - Puri, Gista Alfania; Prameswati, Devi; Nabiha, Fikria Hanifa; Octaviani, Flira Tri; Nugroho, Kayla Aryani Putri; Nuraya, Ahmad Setiawan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyse the factors affecting inflation in Indonesia, focusing on government policies, exchange rate fluctuations, and international trade. Using a descriptive qualitative approach, this study examines the linkages between the government’s fiscal and monetary policies in controlling inflation, the dynamics of the Rupiah exchange rate against the US Dollar, and the role of exports and imports in influencing the domestic inflation rate. The results show that monetary policy through interest rate setting and fiscal policy through government spending significantly affect inflation. Fluctuations in the rupiah exchange rate tend to trigger inflation through increased costs of imported raw materials. In addition, international trade through both exports and imports has the potential to affect inflation through changes in demand and supply of goods in the domestic market. This study provides implications for the formulation of economic policy, particularly in anticipating the impact of external factors on inflation and maintaining price stability.